PENINGKATAN PENGETAHUAN DAN KETERAMPILAN MELALUI DEMONSTRASI DAN SHORT EDUCATION MOVIES TENTANG LUKA BAKAR DI SMKN 3 KOTA PEKANBARU - Febtrina, Rizka; Vanissyah, Janny; Febri, Dea; Qusthia, Hidayatunnisa; Oktavia, Tesa; Hafizah, Esy; Rahmayanti, Amanda; Ramadhan, Intan Tiara; Wati, Willa Sastrida; Putri, Cucu; Baizura, Ning; Utari, Retno Tri (LPPM Institut Pendidikan Nusantara Global, 2023)
Burns are a type of trauma with high morbidity and mortality that require special management from the early (shock phase) to the end phase. Handling of burns in the school environment is still relatively low, one of which is at SMKN 3 Pekanbaru City in the culinary arts department. The importance of appropriate management and the lack of knowledge about treating burns at SMKN 3 Pekanbaru City are the background for this community service. The methods used in this counseling are education, demonstrations and screening of short educational films about burns. The participants in the counseling were 32 students from SMKN 3 Pekanbaru City majoring in culinary arts. This activity starts from the planning stage to the evaluation, implementation will be held on Wednesday 8 November 2023 in the Restaurant room of the Culinary Department of SMKN 3 Pekanbaru City. The level of knowledge was measured using a questionnaire, and wound care skills were assessed using a check list sheet. The results of the counseling show that there is an increase in knowledge and skills regarding handling burns in the early phase. Through this counseling, it is hoped that participants will be able to apply the right steps in treating burns at an early stage.